2008
DOI: 10.1371/journal.ppat.1000012
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Reassortment Events in the Evolutionary History of H1N1 Influenza A Virus Since 1918

Abstract: The H1N1 subtype of influenza A virus has caused substantial morbidity and mortality in humans, first documented in the global pandemic of 1918 and continuing to the present day. Despite this disease burden, the evolutionary history of the A/H1N1 virus is not well understood, particularly whether there is a virological basis for several notable epidemics of unusual severity in the 1940s and 1950s. Using a data set of 71 representative complete genome sequences sampled between 1918 and 2006, we show that segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
216
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(243 citation statements)
references
References 36 publications
10
216
1
6
Order By: Relevance
“…showed that reassortment occurs at rather low rates in viruses of the family Bunyaviridae (Henderson et al, 1995;Nemirov et al, 1999) or of other families (Fraile et al, 1997;Lin et al, 2004;Roossinck, 2002;Bonnet et al, 2005;Miranda et al, 2000;Iturriza-Gó mara et al, 2001;Watanabe et al, 2001;McDonald et al, 2009), which could be due to strong selection acting against reassortants (Brown et al, 2002;Fraile et al, 1997;Escriu et al, 2007). Some viral taxa seem however to show more extensive reassortment (Silander et al, 2005;Lindstrom et al, 2004;Nelson et al, 2008;Khiabanian et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…showed that reassortment occurs at rather low rates in viruses of the family Bunyaviridae (Henderson et al, 1995;Nemirov et al, 1999) or of other families (Fraile et al, 1997;Lin et al, 2004;Roossinck, 2002;Bonnet et al, 2005;Miranda et al, 2000;Iturriza-Gó mara et al, 2001;Watanabe et al, 2001;McDonald et al, 2009), which could be due to strong selection acting against reassortants (Brown et al, 2002;Fraile et al, 1997;Escriu et al, 2007). Some viral taxa seem however to show more extensive reassortment (Silander et al, 2005;Lindstrom et al, 2004;Nelson et al, 2008;Khiabanian et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Genome segmentation complements the high mutation rate of IAV by facilitating reassortment, which can maximize positive intergenic epistasis (2)(3)(4)(5) and allow selective elimination of segments with deleterious mutations (6,7). Although reassortment is the most obvious and best-characterized benefit of segmentation, there are likely additional evolutionary advantages.…”
mentioning
confidence: 99%
“…9,10) Analysis of full genome sequences of representative in‰uenza A (H1N1) viruses from 17 countries andˆve continents that were sampled between 1918 and 2006 shows that all eight segments of the virus have had generally congruent patterns of evolution over time. 11) In‰uenza A (H1N1) abruptly disappeared from humans in 1957 and was replaced by a new reassortant virus called in‰uenza A (H2N2) strain contained three new segments from the avian source and maintained the otherˆve segments from the H1N1 strain of 1918 lineage. 12,14) After this pandemic subtype emerged, human in‰uenza A (H1N1) was not detected again until 1977.…”
Section: Emergence Of Influenza Viruses With Historical Perspectivesmentioning
confidence: 99%